An Essay on the History of Civil Society, Eighth Edition - Ferguson, Adam, 1723-1816 (Salt Lake City, UT : Project Gutenberg, 2005)
"An Essay on the History of Civil Society" by Adam Ferguson is a philosophical work written during the 18th century. This essay explores the development of human societies and the principles underlying civil society, examining topics such as human nature, social structures, and moral sentiments. Ferguson delves into the evolution of man from a state of nature to organized societies, investigating how individual characteristics and societal factors interact to shape civilization. The opening of the essay begins with an exploration of the state of nature, contrasting ideas about human characteristics in their primitive conditions versus their developed states. Ferguson posits that mankind has transitioned from a rudimentary existence to one characterized by civilization, emphasizing the importance of societal bonds and moral sentiments in human development. He critiques various theories that attempt to define human nature based strictly on speculation or conjecture, advocating instead for a focus on observable human behaviors and historical facts. Ferguson argues that individual and collective experiences within society are crucial to understanding humanity, setting the stage for a broader discussion about the consequences of civil and commercial arts on nations. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/An_Essay_on_the_History_of_Civil_Society
Release date is 2005-08-01
Produced by Stan Goodman, William Craig, Charles Franks and the Online Distributed Proofreading Team
Keywords: Civilization -- History; Civil society -- History